2018
DOI: 10.1186/s13071-018-3044-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferases play a role in the detoxification of flumethrin and chlorpyrifos in Haemaphysalis longicornis

Abstract: BackgroundHaemaphysalis longicornis is a tick of importance to health, as it serves as a vector of several pathogens, including Theileria orientalis, Babesia ovata, Rickettsia japonica and the severe fever with thrombocytopenia syndrome virus (SFTSV). Presently, the major method of control for this tick is the use of chemical acaricides. The glutathione S-transferase (GST) system is one mechanism through which the tick metabolizes these acaricides. Two GSTs from H. longicornis (HlGST and HlGST2) have been prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…GSH is a non-enzymatic antioxidant, which could be directly used to scavenge oxygen free radicals to protect the cells (Regoli & Principato, 1995), used as substrate by antioxidant enzymes or conjugated with various endogenous and exogenous substances in a biotransformation reaction catalysed by GST (Regoli, Nigro, & Orlando, 1998). This enzyme can be induced by organic compounds (Hernandez et al, 2018;Hoarau, Gnassia-Barelli, Romeo, & Girard, 2001) and different metals, such as copper (Canesi, Viarengo, Leonzio, Filippelli, & Gallo, 1999;Roméo et al, 2003;Sabatini, Rocchetta, Nahabedian, et al, 2011), manganese and zinc (Di Salvatore et al, 2013). GST not only detoxifies anthropogenic chemicals by biotransformation reactions but also plays an important role in the antioxidant defence (Awasthi, Ramanaa, Chaudhary, Srivastava, & Awasthi, 2017;Dasari, Ganjayi, Oruganti, Balaji, & Meriga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…GSH is a non-enzymatic antioxidant, which could be directly used to scavenge oxygen free radicals to protect the cells (Regoli & Principato, 1995), used as substrate by antioxidant enzymes or conjugated with various endogenous and exogenous substances in a biotransformation reaction catalysed by GST (Regoli, Nigro, & Orlando, 1998). This enzyme can be induced by organic compounds (Hernandez et al, 2018;Hoarau, Gnassia-Barelli, Romeo, & Girard, 2001) and different metals, such as copper (Canesi, Viarengo, Leonzio, Filippelli, & Gallo, 1999;Roméo et al, 2003;Sabatini, Rocchetta, Nahabedian, et al, 2011), manganese and zinc (Di Salvatore et al, 2013). GST not only detoxifies anthropogenic chemicals by biotransformation reactions but also plays an important role in the antioxidant defence (Awasthi, Ramanaa, Chaudhary, Srivastava, & Awasthi, 2017;Dasari, Ganjayi, Oruganti, Balaji, & Meriga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study suggested that increased GST activity was one of the mechanisms underlying chlorpyrifos resistance in L. migratoria . The silencing of HlGST2 resulted in increased mortality in Haemaphysalis longicornis larvae exposed to chlorpyrifos . Two epsilon GST genes ( BdGSTe2 and BdGSTe4 ) were significantly overexpressed in malathion‐resistant strains and played a key role in the generation of malathion resistance in Bactrocera dorsalis (Hendel) .…”
Section: Discussionmentioning
confidence: 99%
“…GGT is an enzyme present in cell membranes and is involved in cross-cell-membrane trafficking of amino acids and peptides and in glutathione metabolism (Mulenga and Erikson, 2011). Glutathione S-transferases (GST) are proteins that belong to a multigene family and play a central role in the detoxification of xenobiotic compounds (de Lima et al, 2002), with increased expression levels being correlated with insecticide resistance in various organisms, including ticks (Nandi et al, 2015;Hernandez et al, 2018). GGT plays key roles in intracellular reduced glutathione (GSH) homeostasis by breaking down the extracellular molecule and providing cysteine for intracellular de novo synthesis of GSH (Accaoui et al, 2000;Zhang et al, 2005).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
“…The authors also related that increased expression of GGT during oxidative stress facilitates GSH turnover, de novo GSH synthesis, and metabolism and detoxification of GSH conjugates, increasing cell resistance to subsequent stress. In Haemaphysalis longicornis, the analysis of two GSTs using realtime PCR showed that gene expression increases continuously in salivary glands and other organs of the tick as blood-feeding progresses until female engorgement, demonstrating the possible role of GSTs in coping with oxidative stress caused by bloodfeeding (Hernandez et al, 2018).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
See 1 more Smart Citation